Reconstruction of solid models from sketches including curves with inductive learning technique. Issue 5 (29th July 2017) - Tanaka, Masaji; Takamiya, Yuki; Tsubota, Naoki; Asanuma, Shigeyuki; Iwama, Kenzo
ABSTRACT: Since decades, many methods have been proposed to automatically reconstruct solid models from their sketches. However, it was difficult for the methods to handle sketches including curved lines such as cylinders. Recent years, the authors have proposed a method for the reconstruction of sketches including curves. In the method, the features of sketches of cuboids, cylinders, etc. were defined beforehand. When a sketch was input to the method, each feature was detected and extracted repeatedly from that, and a solid model was obtained by combining 3D features. However, after a feature was extracted from a sketch, some restoration process was needed because of the next feature extraction. Since the restoration process was ad hoc, its programming tended to be difficult. In this paper, a new method is proposed. This method would formalize and simplify the restoration process by applying our inductive learning technique. Although the learning technique had an issue that properties of geometric elements would increase exponentially, this method could prevent the increase by applying our IFOG (Inductive Functional prOgramming for Geometric processing) technique. The effectiveness of this method is indicated by three examples in this paper. GRAPHICAL ABSTRACT: